Application of a compact trickle-bed bioreactor for the removal of odor and volatile organic compounds emitted from a wastewater treatment plant. (15th April 2019) - Kasperczyk, Damian; Urbaniec, Krzysztof; Barbusinski, Krzysztof; Rene, Eldon R.; Colmenares-Quintero, Ramon F.
Abstract: A compact trickle-bed bioreactor (CTBB) was tested for the removal of volatile organic compounds (VOCs) and hydrogen sulphide (H2 S) present in the exhaust air of a wastewater treatment plant. At gas-flow rates varying between 2.0 and 30.0 m 3 /h and for specific pollutant loads up to 20 g/(m 3 ·h), removal efficiencies for H2 S and VOC were >95%. The CTBB was designed for a maximum H2 S concentration of ∼200 ppm and removal efficiencies >97% were noticed. VOC concentrations were in the range of 25–240 ppmv and the removal efficiency was in the range of 85–99%. Possible consequences of an excessive pollutant overload and the time required for regenerating the microbial activity and reviving stable process conditions in the CTBB were also investigated. An increase in the H2 S concentration from 400 to 600 ppmv for a few hours caused bioreactor poisoning; however, when original H2 S concentrations were restored, stable CTBB operation was ascertained within 3 h. Graphical abstract: Image 1094731 Highlights: Removal of volatile organic compounds (VOC) and hydrogen sulfide (H2 S) is reported. The pollutants were present in the exhaust air of a wastewater treatment plant. A compact trickle-bed bioreactor (CTBB) was tested for pollutant loads <20 g/(m 3 h). The efficiency of CTBB was: H2 S removal >97% and VOC removal >85%.